EKG Teaching Rounds A Case-Based Guide - Tannenbaum, Lloyd; Bridwell, Rachel E.; Inman, Brannon L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is a short-form guide designed to fill a training gap in medical education. It is a reference that will help interns and junior residents understand and appropriately respond to real world situations that they will be encountering as newly minted physicians. The book outlines a basic methodology for electrocardiogram (EKG) interpretation and sets a framework for the junior resident physician to use to approach every EKG. It describes common dysrhythmias that residents will often encounter, on the wards, in the emergency department, and in clinic. It uses many high-quality images to prime junior learners in the interpretation and recognition of high yield EKGs. Chapters address commonly encountered pathology, such as atrio-ventricular blocks, tachydysrhythmias, acute coronary syndrome, and syncope. The conversational tone of this book is designed to mimic how staff physicians talk to senior medical students and junior residents, maximizing readability to enhance retention. EKG Teaching Rounds is a case-based book that will quickly become an essential reference text for medical professionals in training who are looking to advance their knowledge of EKG interpretation. This book is relevant for every medical specialty and every level of medical education.
Chapter 1: The Basics -- Chapter 2: Conduction Blocks -- Chapter 3: Tachydysrhythmias -- Chapter 4: Bradydysrhythmias -- Chapter 5: Electrolytes -- Chapter 6: Syncope -- Chapter 7: Acute Coronary Syndrome. .
Keywords: Cardiology; Cardiology; Electrocardiography